Feeding Habitats Selection of Waterbirds in Loktak Lake, Manipur, India - Meitei, N. Sony; Singh, R.K. Birjit; Meetei, Sh. Bijen; Meitei, N. Mohilal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Waterbirds utilized the wetland primarily as a foraging ground and the significant predator-prey relationship between birds and fish, plants and benthic invertebrates can observe. Water depth is also an important variable factor that affects the use of wetland habitats by waterbirds for their foraging. The relationship based on water depth directly determines the accessibility of foraging habitats for waterbirds because of the restrictions of their morphology and feeding resources. The present study deals on foraging habitats of waterbirds in three guilds of Loktak Lake, Manipur. A total of 20 species of waterbirds, including resident and migratory, were analyzed for their feeding and foraging habitats. The species of the first and second guild are mainly non-vegetarian that feeds on fish and aquatic vertebrates. In the third guild, the maximum population was observed in Lesser Whistling Duck Dendrocygna javanica. Many waterfowls mostly forage the third guild that feeds on floating macrophytic vegetation. The main objectives of the study was to documented and analyse the feeding behavior and foraging habitats of waterbirds in the Loktak Lake.